2017
DOI: 10.1016/j.toxlet.2016.12.015
|View full text |Cite
|
Sign up to set email alerts
|

4-Nonylphenol induces autophagy and attenuates mTOR-p70S6K/4EBP1 signaling by modulating AMPK activation in Sertoli cells

Abstract: The estrogenic chemical 4-nonylphenol (NP) is known to impair testicular devolopment and spermatogenesis in rodents. The objective of this study was to explore the effects of NP on autophagy induction and AMPK-mTOR signaling pathway in Sertoli cells (SCs), which are the "nursemaid cells" for meiosis of spermatocytes. In this study we exposed 7-week-old male rats to NP by intra-peritoneal injection at 0, 20, 50 or 100 mg/kg body weight/2 days for 20 consecutive days. Our results showed that exposure to NP dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 49 publications
2
42
0
Order By: Relevance
“…This was confirmed by upregulation of LC3-II using western blot, which was statistically significant (Figure 7C) and downregulation of p62 in ethanol-exposed SCs compared to the control (Figure S5). Blocking autophagy with 3-methyladenine (3-MA), an inhibitor of early autophagosome formation [44,45], resulted in a marked reduction of cell viability in cultured ethanol-treated SCs (Figure 7D), indicating the prosurvival role of autophagy as supported by other studies [19,20,34,41,44,45]. …”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…This was confirmed by upregulation of LC3-II using western blot, which was statistically significant (Figure 7C) and downregulation of p62 in ethanol-exposed SCs compared to the control (Figure S5). Blocking autophagy with 3-methyladenine (3-MA), an inhibitor of early autophagosome formation [44,45], resulted in a marked reduction of cell viability in cultured ethanol-treated SCs (Figure 7D), indicating the prosurvival role of autophagy as supported by other studies [19,20,34,41,44,45]. …”
Section: Resultssupporting
confidence: 65%
“…This cytoprotective role for autophagy has also been observed in thymic macrophages [12], hepatocytes [31,44] and astrocytes [34] with the same animal model of acute ethanol toxicity. To provide direct proof for the prosurvival role of autophagy in SCs, the authors exposed cultured SCs to various concentrations of ethanol and found that blocking of autophagy by 3-MA resulted in reduction of viability, as also observed in similar studies of cultured SCs with various models of acute stress [19,20] and in cultured hepatocytes exposed to ethanol [44]. Blocking autophagy with 3-MA mitigated viability both in ethanol-exposed SCs and in untreated cells, indicating that autophagy is essential for the survival of SCs under normal and ethanol-exposed conditions [44].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, AMPK activation inhibits cell proliferation via the upregulation of the insulin receptor substrate (Fisher, Gao, Han, Holloszy, & Nolte, ; Harrington et al, ; Shah, Wang, & Hunter, ; Um et al, ) and the suppression of mTOR pathway (Johnson, Rabinovitch, & Kaeberlein, ; Mihaylova & Shaw, ; Patel et al, ). The AMPK signaling pathway is involved in the disruption of SC polarity (Tanwar, Kaneko‐Tarui, Zhang, & Teixeira, ), dysregulated energy metabolism (Bertoldo et al, ), autophagy, and apoptosis in SCs (Duan et al, ; Duan et al, ). These findings are coincided with AICAR‐induced inhibition of SC proliferation via the activation of AMPKα2 based on the GO enrichment and KEGG pathway analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that autophagy has a protective role in Sertoli cells under various pathological conditions (Aslani et al., ; Yin et al., ). The autophagy inhibitor 3‐MA enhances xenoestrogen 4‐nonylphenol‐induced rat Sertoli cell apoptosis and necrosis (Duan et al., ). Autophagy‐mediated degradation of PALIM1 in mouse Sertoli cells is important for the proper assembly of the ectoplasmic specialization (ES), and the ES is essential for Sertoli‐germ cell communication (Liu et al., ).…”
Section: Discussionmentioning
confidence: 99%